2016
DOI: 10.1111/sms.12698
|View full text |Cite
|
Sign up to set email alerts
|

Return to sport matters—longer‐term quality of life after ACL reconstruction in people with knee difficulties

Abstract: Many individuals experience long-term quality of life (QOL) impairment following anterior cruciate ligament reconstruction (ACLR). Factors contributing to poor QOL and psychological health >5 years after ACLR remain unclear. This study aimed to describe QOL and psychological health outcomes in people with knee difficulties (pain, symptoms, or functional limitations) 5-20 years following ACLR and identify factors explaining variability in these outcomes. Participants with knee difficulties 5-20 years following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 47 publications
2
74
1
Order By: Relevance
“…Even though larger group differences were seen for the other KOOS subscale values, the CIs were wider than for KOOS ADL, which may explain the lack of statistically significant differences. Filbay et al 39 reported that subjects who returned to competitive sport at the same or higher level had 12 points higher knee-related quality of life score compared with those who did not return to sport 5–20 years after the ACLR. The greater difference observed by Filbay et al may relate to their inclusion of ACLR patients with knee pain and symptoms, and with shorter follow-up time, which would result in a different sample from the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Even though larger group differences were seen for the other KOOS subscale values, the CIs were wider than for KOOS ADL, which may explain the lack of statistically significant differences. Filbay et al 39 reported that subjects who returned to competitive sport at the same or higher level had 12 points higher knee-related quality of life score compared with those who did not return to sport 5–20 years after the ACLR. The greater difference observed by Filbay et al may relate to their inclusion of ACLR patients with knee pain and symptoms, and with shorter follow-up time, which would result in a different sample from the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Further, due to the limited number of persons with MRI-defined OA, the current analyses could not assess the interaction between injury history and MRI-defined OA; therefore, although both appear to impact knee-related quality of life independently, their additive effect 3–10 years following a youth sport-related knee injury remains unknown. Other factors that may contribute to knee-related quality of life include the ability to return to sport and subsequent and contralateral knee surgery 17. Accordingly, future investigations aimed at further elucidating the relationship between knee-related quality of life and MRI-defined OA following sport-related knee injury should aim for a larger sample size that enable multivariable analyses with more sophisticated models that consider the interaction of injury history and MRI-defined OA and other potential explanatory factors.…”
Section: Discussionmentioning
confidence: 99%
“…Following this, 162 people with knee difficulties 5–20 years after ACL reconstruction completed a range of patient-reported measures (including four QOL measures) 4. Regression analysis was used to identify factors explaining variability in QOL.…”
Section: How Did I Do It?mentioning
confidence: 99%